Discovery of dibenzyl amide derivatives as novel CXCR4 modulators against inflammatory bowel disease - Xiaoying Jiang; Liuxin Lu; Jiahui Wang; Meng Yu; Rui Wu; Rui Zhao; Hao Wen; Renren Bai (Elsevier, 2024)
The CXCR4/CXCL12 chemokine axis demonstrates significant potential in the treatment of inflammatory bowel disease (IBD) due to its crucial roles in inflammatory and immune responses. Modulating the CXCR4/CXCL12 pathway can be an effective therapeutic approach to ameliorate the inflammatory state of IBD. In this study, a novel series of meta-dibenzyl amide derivatives were designed and synthesized based on the lead compound AMD3100 and its structurally modified derivatives. Both in vitro and in vivo assays conclusively established that these compounds exhibited potent CXCR4 antagonism and anti-inflammatory activity. Compound 5t demonstrated superior inhibitory rates of binding affinity and chemotaxis of CXCR4+ cells compared to AMD3100. Furthermore, compound 5t notably reduced swelling volume and tissue thickness in the carrageenan-induced mouse paw edema model. Most importantly, in the dextran sodium sulfate (DSS)-induced colitis model, compound 5t significantly mitigated colonic inflammation on both macroscopic and microscopic levels, while suppressing the expression of inflammatory factors and myeloperoxidase (MPO). These findings unequivocally establish the immense potential of compound 5t in the treatment of IBD.